Versatile Synthesis of Symmetrical Carbazole-Based Ligand Precursors via Regioselective Aromatic Bromination - Rembiak, Andreas; Koskinen, Ari M. P. (Synthesis, 2015)
A highly efficient synthetic route towards dibrominated, substituted carbazoles via an environmentally benign, regioselective bromination as the key step has been developed. Electron-rich and electron-deficient aromatic as well as aliphatic groups are well tolerated enabling access to these versatile ligand precursors in high overall yields. On larger scale the whole sequence can be performed under chromatography-free conditions.
Keywords: carbazoles; heterocycles; tridentate ligands; regioselective bromination; chiral oxazolines